Emisja obligacji jako czynnik poprawy stabilności i konkurencyjności banków spółdzielczych - Kozak, Sylwester (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The amount of own funds of banks has a signifi cant impact on the stability of their operations and ability to absorb losses. In the indirect way it determines the value of lending activity, the level of competitiveness and position in the banking market. This article aims to analyze the regulations and the scale of bond issuance held by cooperative banks and the role of funding to improve their stability and competitiveness in the banking market in 2010–2011. The results indicate that in Poland and other EU countries, cooperative banks are important providers of credit, especially for SMEs. Raising equity through issuance of bonds may extend the area of operation and increase the total amount of credit and commitment to individual enterprise.